Exploring the Implications of a Needs-Based Pharmacy Education Framework Modelled on Population Health: Perspective from a Developing Country - Angeni Bheekie; Mea Van Huyssteen; Renier Coetzee (MDPI AG, 2019)
Globally, health education reform is directing efforts to strengthen the health system through collaboration between health education and health services. However, collaborative efforts vary between developed and developing countries as the health needs, economic constraints, and resource availability differs. In developing countries, resource allocation is weighed in favor of interventions that will benefit the majority of the population. The question that emerges is: How could health education, service, and research activities be (re-)aligned to optimize return on investment for the health system and society at large? This paper proposes a needs-based pharmacy educational approach by centralizing population health for a developing country like South Africa. Literature on systems-based approaches to health professional education reform and the global pharmacy education framework was reviewed. A needs-based pharmacy educational approach, the population health model which underpins health outcome measurements to gauge an educational institution’s effectiveness, was contextualized. An evaluation framework to determine the pharmacy school’s effectiveness in strengthening the health system could be applied. A needs-based pharmacy educational approach modeled on population health could: Integrate resources from education, service, and research activities; follow a monitoring and evaluation framework that tracks educational outcomes; and engage with external stakeholders in curricular development and assessment.